2015
DOI: 10.47125/jesam/2015_1/06
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Larval Rearing Temperature and Host Plant Condition on the Development, Survival, and Coloration of African Armyworm, Spodoptera exempta Walker (Lepidoptera: Noctuidae)

Abstract: Effects of temperature and host plant condition on insect development have been examined in a number of studies but their combined effect is not well investigated. In this study the effects of varying temperatures and host plant conditions and its interaction on development, survival, and coloration of solitarious and gregarious forms of African armyworm (AW), Spodoptera exempta, an outbreak pest species, were studied under laboratory condition. Rearing temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…Nonetheless, the areas where outbreaks occur (which we modelled) are not always the same as the ones where low-density populations settle (which we did not explicitly model). Temperature changes affect the species distribution too because, being ectotherms, their development and survival are temperature-dependent 56 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, the areas where outbreaks occur (which we modelled) are not always the same as the ones where low-density populations settle (which we did not explicitly model). Temperature changes affect the species distribution too because, being ectotherms, their development and survival are temperature-dependent 56 .…”
Section: Discussionmentioning
confidence: 99%
“…2 A). Low environmental suitability coincides with arid or semi-arid areas, which may seem evident as extreme temperatures and dry conditions are not ideal for the development of its eggs and pupae 56 , 57 . Indeed, water and ambient humidity scarcity can affect the water balance of insects, impacting their survival, development and even their population dynamics, as seen in similar species, the FAW 58 .…”
Section: Discussionmentioning
confidence: 99%
“…(2020) reported total larval development periods in the 10 to 14 days range (average of 11.38 ± 0.25 days) at 30 o C, and between 10 to 12 days at 32 o C. Temperature greatly influences the rate of development, and by extension, the biology, occurrence, abundance, and distribution of insect pests (Howe, 1967;Porter, 1991;Tobin et al, 2003;Abrahams et al, 2017;Du Plessis et al, 2020). In the same vein, the number of instars comprising an insect larval stage is significantly influenced by rearing temperature and diet (Ali et al, 1990;Aguilon et al, 2015;Rojas et al, 2018). Furthermore, S. frugiperda larva developed through six instars on natural maize leaf diet at an ambient temperature of approximately 30 o C. Du Plessis et al (2020) also reported an optimum temperature of 30 o C for the development of S. frugiperda larvae, even though it may range between 26 -30 o C. Sharanabasappa et al (2018) reported a 9 -12 days pupation period for S. frugiperda in India.…”
Section: Discussionmentioning
confidence: 99%
“…Temperature in particular appears to have clear effects on intraspecific variation in lepidopteran colouration (Hill et al, 2021). Higher growing temperatures resulted in lighter colouration in African armyworm ( Spodoptera exampta ) larvae, Asian comma ( Polygonia caureum ) pupae and speckled wood ( Parage aegeria ) adults (Aguilon et al, 2015; Taylor‐Cox et al, 2020; Yamanaka et al, 2012). Similarly, monarch larvae reared in the laboratory at warmer temperatures displayed thinner black stripes compared to those reared at colder temperatures (Davis et al, 2005; Solensky & Larkin, 2003).…”
Section: Introductionmentioning
confidence: 99%